Muslim Marriage in Western Courts: Lost in Transplantation - Fournier, Pascale (Cultural Diversity and Law, 2010)
This book describes and analyzes the notion of Mahr, the Muslim custom whereby the groom has to give a gift to the bride in consideration of the marriage. It explores how Western courts, specifically in Canada, the United States, France, and Germany, have approached and interpreted Mahr. Returning to the overarching concept of liberalism, the book proposes that distributive consequences rather than recognition occupy central place in the evaluation of the legal options available to Muslim women upon divorce.